(3fXQjI GdJfXje (B/s - (3SGde, eMeO Ydjs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2009)
(3acQI JGQjNjI Yf GOGQI GdefXeGJ , GJLGg GdYdGbGJ GdGfSGfjI , GdGJLGg GdMOjK aj GdacQ GdGOGQj , GdefXeGJ cfXGe eaJhM , fehPL GdfXGe GdYGe , GdfXe GdaQYjI GdeJQGHWI , GdfXe hGdXQha GdNGQLjI ddefXeI GdeOGNd GdeNJdaI dOQGSI GdJfXje , fXQjI GdJfXje GdcdGSjcjI , fXQjI GdHjQhbQGWjI , fehPL eQJhf ddHjQhbQGWjI, fehPL SdRfjc , fehPL LhdOfQ, fXQjI GdGOGQI GdYdejI , fXQjGJ GdJbSje GdGOGQj , fXQjI ehfj h Qdjdj , fXQjGJ GdYdGbGJ GdGfSGfjI , fXQjI GdadSaI GdGOGQjI (B((3OhLdGS eGcLQhLQ(B)(3, fXQjGJ GdJfXje GdeYOdI , fXQjI GdJfXje GdGLJeGYj , fXQjI GdJfGbV Hjf GdaQO h GdJfXje , fXQjI GdJaGYd , fXQjGJ GdJfXje GdMOjKI , fXQjI GJNGP GdbQGQGJ h GdJhGRf GdJfXjej , GdfXQjI GdJLejYjI, GdeONd GdJcGedj dfXQjI GdJfXje (B.s
(3eQGLY U(B.208s
Keywords: (3GdEOGQIs; (3GdJfXjes; (3GdacQ GdGOGQjs; (3GdefXeIs